Identifikasi Nilai Keacakan Berdasarkan Reposisi Fungsi XOR Pada Blok Kedua LFSR A5/1 - Pallangan, Jorghie Theodore Kenzo; Wowor, Alz Danny (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research plans a random number generation method using the Linear Feedback Shift Register (LFSR) method with the A5/1 scheme which involves three feedback functions. XOR is used to determine the new output bit value in the next iteration in the feedback mechanism. The test material produces random output for an input using Run Test, Mono Bit, and Block bit. Tests using three feedback functions were carried out to compare with previous research which generated random numbers. Testing of plaintext and ciphertext encryption shows a very small level of correlation with an average value close to 0. The use of LFSR with the A5/1 scheme which involves three XOR functions, creates random output and can be used against Stream Chipers.